Nachtrag zu: Cerastium rivulariastrum Moschl & Pedersen n.sp. und Cerastium rivulare Camb. emend. Moschl, Darwiniana 16(1-2):116-128, 1970. - Moschl, W.; Pedersen, T. Myndel
vol: 16 / no: 3-4 / p.800 / Inv: 06-R00179-ej.1 01-R08785-ej.2 02-R05947-ej.3 / ST: AR-D/1 v 16 no 3/4
En: vol 16, no 3-4
Keywords: Cerastium